The use of herbs as an alternative method of healing in contemporary Nigerian society (2015)
Africa has been highly affected by Western influence but in spite of the massive pressure of Western civilisation, Africans still practice traditional healing. This paper is set out to analyse the reasons why traditional healing is relevant to Contemporary Nigeria. However, emphasis is placed on Yoruba herbal medicine as a means of healing. It discusses the nature of Yoruba herbal medicine and reasons why it is unique as a means of healing. The paper employs relevant literature on the subject of Yoruba herbal medicine, places special attention on the Contemporary relevance of the use of herbs and examines the reasons why people prefer traditional herbs to orthodox medicine or use herbs simultaneously with orthodox medicine. The challenges hindering the use of Yoruba herbal medicine are highlighted, and relevant recommendations are made to enhance the use of Yoruba herbal medicine. The theoretical framework for this paper is the Pragmatic theory of Truth of Hilary Putnam. Pragmatism is a practical approach to issues that is optimistic, in which a concept is justified in its ability to work and in this case, herbal medicine and its practical relevance today.